B-Acute Lymphoblastic Leukemia: Disparate Genetic Aberrations in Children. (21st September 2018) - Reddy, Amit; Espinoza, Ingrid; Cole, Dana; Schallheim, Jason; Poosarla, Teja; Bhanat, Eldrin; Zhou, Yunyun; Zabaleta, Jovanny; Megason, Gail; Gomez, Christian
Abstract: Background: B-acute lymphoblastic leukemia (B-ALL) is the most common form of cancer in pediatric patients, comprising more than 30% of all childhood malignancies. The survival of B-ALL patients is significantly lower in African American (AA) children compared to European American children (EA). This disparity is not related to socioeconomic variables, suggesting a molecular basis for the lower survival rates of African Americans. Here we present a whole-exome sequencing (WES) study showing race-specific genetic variations that may play a role on the disparate outcomes among AA and EA children with B-ALL. Patients and Methods: Five AA and 15 EA patients ranging in age from 1 to 18 years were enrolled. Median blast percentage was 94.8% (64.5%-99.9%). Frozen bone marrow aspirate was used to extract DNA and WES was performed, focusing on race- and B-ALL–specific germline mutations. Results: Specific germline mutations were identified in the most widely accepted cancer-related genes related to B-ALL. Most genetic variants (n = 339) were shared between AA and EA children. Some genetic aberrations were only uniquely identified in AA (n = 58) and others in EA (n = 52). The ingenuity pathway analysis revealed these genes clustered in race-specific canonical pathways. In AA, the genetic aberrations clustered in canonical pathways related to telomerase signaling and cancer signaling. In EA, the unique genetic aberration clustered in pathways related to stem cell pluripotency and hereditary cancer. Conclusions: Our study revealed aberrant genetic aberrations in signaling networks that may contribute to race-specific aspects of leukemogenesis. Our results suggest the value of WES as a tool for development of individual gene signatures and gene scores for AA and EA children afflicted by B-ALL. These findings may ultimately impact disease management and contribute to the elimination of disparate outcomes in AA children with B-ALL.